The Right to Be Forgotten and Digital Reputation: A Normative Analysis within Indonesian Cyber Law - Elinda Novita Dewi; Sunusi Dauda (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid expansion of digital infrastructures and algorithmic information systems has intensified debates concerning the right to be forgotten (RTBF) and the protection of digital reputation. This study conducts a doctrinal-normative analysis of RTBF within Indonesian cyber law, examining its statutory basis under the Electronic Information and Transactions Law and the Personal Data Protection framework. Through systematic statutory interpretation, conceptual analysis, and limited comparative evaluation with transnational data protection standards, the research identifies significant normative fragmentation in the regulation of erasure rights. Sectoral examination of blockchain immutability, artificial intelligence–generated deepfakes, child digital exploitation, doxing, digital banking, and digital inheritance reveals structural tensions between reputational protection, transparency obligations, technological permanence, and legal certainty. The study proposes a structured balancing model grounded in legitimacy of purpose, proportionality, public interest, technological feasibility, and evidentiary integrity. By reconceptualizing digital reputation as a dignity-based and sovereignty-linked legal interest, this research advances a coherent normative framework that strengthens doctrinal clarity and supports principled adjudication of erasure claims in Indonesia’s evolving cyber governance architecture.